Dengue Virus Uses a Non-Canonical Function of the Host GBF1-Arf-COPI System for Capsid Protein Accumulation on Lipid Droplets - Iglesias, Nestor Gabriel (2015)
Dengue viruses cause the most important human viral disease transmittedby mosquitoes. In recent years, a great deal has been learnedabout molecular details of dengue virus genome replication; however,little is known about genome encapsidation and the functions of theviral capsid protein. During infection, dengue virus capsid progressivelyaccumulates around lipid droplets (LDs) by an unknown mechanism.Here, we examined the process by which the viral capsid is transportedfrom the endoplasmic reticulum (ER) membrane, where the protein issynthesized, to LDs. Using different methods of intervention, we foundthat the GBF1-Arf1/Arf4-COPI pathway is necessary for capsid transportto LDs, while the process is independent of both COPII componentsand Golgi integrity. The transport was sensitive to Brefeldin A, while adrug resistant form of GBF1 was sufficient to restore capsid subcellulardistribution in infected cells. The mechanism by which LDs gain or loseproteins is still an open question. Our results support a model in whichthe virus uses a non-canonical function of the COPI system for capsidaccumulation on LDs, providing new ideas for antiviral strategies.